INTERAKSI SOSIAL MASYARAKAT PENDATANG DENGAN MASYARAKAT LOKAL DI RT.04 KELURAHAN CINTA RAJA KECAMATAN - Suciati Suciati; Yusnaini Yusnaini; Safira Soraida (Jurnal Media Sosiologi (JMS), 2021)
Social interaction is the main condition for the occurrence of social activities. Social interaction is also useful for studying and studying many problems in society. This study aims to determine the form of social interaction that occurs between the immigrant community and the local community as well as the driving and inhibiting factors for the occurrence of social interaction between the immigrant community and the local community in RT.04. This research uses descriptive qualitative research methods. Determination of informants in this study was carried out purposively with the number of informants as many as 12 people consisting of main informants and as many as 3 people from supporting informants. Data collection techniques in this study were observation, in-depth interviews with key informants and supporting informants and documentation results. The results of this study indicate that there are forms of social interaction, namely associative forms and dissociative forms. This study also shows that there are encouraging and inhibiting factors in social interaction.